Anti-HIV Activities and Mechanism of 12-O-Tricosanoylphorbol-20-acetate, a Novel Phorbol Ester from Ostodes katharinae - Chen, Huan (Molecules, 2017)
APOBEC3G is a member of the human cytidine deaminase family that restricts Vif-deficient viruses by being packaged with progeny virions and inducing the G to A mutation during the synthesis of HIV-1 viral DNA when the progeny virus infects new cells. HIV-1 Vif protein resists the activity of A3G by mediating A3G degradation. Phorbol esters are plant-derived organic compounds belonging to the tigliane family of diterpenes and could activate the PKC pathway. In this study, we identified an inhibitor 12-O-tricosanoylphorbol-20-acetate (hop-8), a novel ester of phorbol which was isolated from Ostodes katharinae of the family Euphorbiaceae, that inhibited the replication of wild-type HIV-1 and HIV-2 strains and drug-resistant strains broadly both in C8166 cells and PBMCs with low cytotoxicity and the EC(50) values ranged from 0.106 μM to 7.987 μM. One of the main mechanisms of hop-8 is to stimulate A3G expressing in HIV-1 producing cells and upregulate the A3G level in progeny virions, which results in reducing the infectivity of the progeny virus. This novel mechanism of hop-8 inhibition of HIV replication might represents a promising approach for developing new therapeutics for HIV infection.